1999
DOI: 10.4269/ajtmh.1999.61.850
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arthropod saliva antibodies among residents of a community at high risk for Lyme disease in California.

Abstract: Abstract. The role of the western black-legged tick (Ixodes pacificus) versus that of other potential arthropod vectors in the epidemiology of Lyme disease was evaluated by determining the prevalence of anti-arthropod saliva antibodies (AASA) among residents (n ϭ 104) of a community at high-risk (CHR). Salivary gland extracts prepared from I. pacificus, the Pacific Coast tick (Dermacentor occidentalis), the western cone-nose bug (Triatoma protracta), and the western tree-hole mosquito (Aedes sierrensis) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 58 publications
0
23
0
2
Order By: Relevance
“…Previous studies have shown that bioactive molecules in arthropod saliva, injected in human skin during the vector bites, could induce host immune reactions [57]. Recent studies have demonstrated the usefulness of anti-saliva Ab response for measuring exposure of humans to arthropods bites, such as, ticks [8] sand fly [9,10], Glossina [11] and mosquitoes [12–19]. Additionally, human Ab IgG response to whole saliva was identified as pertinent tool for evaluating efficacy of vector control against Anopheles [20,21], Phlebotomus [22] and Aedes albopictus [23].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that bioactive molecules in arthropod saliva, injected in human skin during the vector bites, could induce host immune reactions [57]. Recent studies have demonstrated the usefulness of anti-saliva Ab response for measuring exposure of humans to arthropods bites, such as, ticks [8] sand fly [9,10], Glossina [11] and mosquitoes [12–19]. Additionally, human Ab IgG response to whole saliva was identified as pertinent tool for evaluating efficacy of vector control against Anopheles [20,21], Phlebotomus [22] and Aedes albopictus [23].…”
Section: Introductionmentioning
confidence: 99%
“…16 At the time of biting, the female mosquito injects saliva containing bioactive molecules, including vasodilators and anticoagulants, that make the blood meal possible. 17,18 Human Ab responses to the saliva of Triatoma , vectors of Chagas disease, 19 Ixodes ticks, vectors of Borrelia bugdorferi , 20 This work addresses a potentially important application of this "saliva" biomarker as an immunological tool to evaluate the efficacy of ITN-based strategies. Human immunoglobulin G (IgG) responses to whole An.…”
Section: Introductionmentioning
confidence: 99%
“…11. Finally, defining the most abundant antigens or those that may effectively help ticks to feed or transmit Borrelia could be an effective approach to develop a protective vaccine directed toward tick salivary molecules (Lane et al, 1999). , 1907-1996.…”
Section: Group 16: Housekeeping Cdnamentioning
confidence: 99%